HRM Role in Managing Corporate Sustainability during Covid-19 Pandemic Situation: A Case Study of The Westin Resort Nusa Dua - Puspita, Ni Putu Lianda Ayu; Astawa, I Putu; Triyuni, Ni Nyoman; Astuti, Ni Wayan Wahyu (Jurnal Bali Membangun Bali, 2023)
Purpose: This study aims to determine HRM practices prior to the outbreak of the Covid-19 pandemic and identify the role of HR in managing company sustainability in the Covid-19 pandemic situation. Research methods: The research uses a qualitative approach through the case study method. Data collection techniques through participatory observation and interviews with 1 key informant and 8 supporting informants who are employees of the hotel. Qualitative data analysis starts from data reduction, data presentation and then drawing conclusions. Result and discussion: The results of the study revealed that HRM practices prior to the outbreak of the Covid-19 pandemic were carried out in accordance with applicable standard operating procedures related to recruitment and selection, training and human resource development, and performance appraisal. In the Covid-19 condition, HR plays a role in empowering human resources, carrying out economic activities, generating profits and maintaining service quality to get customer satisfaction. Implications: Several theoretical reviews reveal corporate sustainability indicators such as human resource empowerment, economy, profit and customer satisfaction. While the results of this study provide color to the theory of corporate sustainability by presenting the owner and technology as the main role in the company's sustainability.